The Hip-Hop Underground and African American Culture - Peterson, J. author. aut Link
XIII, 187 p.
Keywords: The underground is a multi-faceted concept in African American culture. Peterson uses Richard Wright, KRS-One, Thelonius Monk, and the tradition of the Underground Railroad to explore the manifestations and the attributes of the underground within the context of a more panoramic picture of African American expressivity within hip-hop.